AMYOBA DIZENTERIYASI, PARAGEMOLITIK, NAG -VIBRIONLAR, TIBBIYOT AMALIYOTIDAGI AHAMIYATI VA BAKTERIOLOGIK DIAGNOSTIKASI - Umida Esirgapova Xasanovna,; Rajabova Azizabo, (TADQIQOTLAR, 2026)
Abstract This  research  provides  an  extensive  academic  and  clinical  inquiry  into  the microbiological characteristics and diagnostic protocols of amoebic dysentery and non-cholera  vibrios,  specifically  Vibrio  parahaemolyticus  and  NAG-vibrios.  The  study evaluates  the  etiological  significance  of  Entamoeba  histolytica  in  gastrointestinal pathology and its potential for extraintestinal complications, such as hepatic abscesses. Furthermore, it examines the emerging public health threat posed by halophilic vibrios in the  context of  foodborne infections.  By  analyzing  contemporary  bacteriological, serological, and molecular diagnostic methodologies, the article highlights the critical importance  of  precise  laboratory  identification  in  clinical  practice.  The  findings emphasize that differential diagnosis is essential for effective therapeutic intervention and the prevention of widespread epidemiological outbreaks.